2017
DOI: 10.1021/acsmacrolett.6b00899
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Poly(ionic liquid) Diblock Copolymers Obtained by Cobalt-Mediated Radical Polymerization-Induced Self-Assembly

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 35 publications
0
64
0
Order By: Relevance
“…As can be easily imagined, the structure of the cationic moiety can be adjusted as well. Similarly, ionic liquid monomers based on N ‐vinyl‐3‐alkylimidazolium bromide with tunable length of the alkyl groups suitable for aqueous dispersion polymerization were also reported . Interestingly, rigid rods over a wide range of composition were obtained even at low solids via aqueous polymerization of N ‐vinyl‐3‐dodecyl imidazolium bromide (C 12 VImBr) mediated by a neutral PEG‐CTA .…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
See 1 more Smart Citation
“…As can be easily imagined, the structure of the cationic moiety can be adjusted as well. Similarly, ionic liquid monomers based on N ‐vinyl‐3‐alkylimidazolium bromide with tunable length of the alkyl groups suitable for aqueous dispersion polymerization were also reported . Interestingly, rigid rods over a wide range of composition were obtained even at low solids via aqueous polymerization of N ‐vinyl‐3‐dodecyl imidazolium bromide (C 12 VImBr) mediated by a neutral PEG‐CTA .…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
“…Similarly, ionic liquid monomers based on N ‐vinyl‐3‐alkylimidazolium bromide with tunable length of the alkyl groups suitable for aqueous dispersion polymerization were also reported . Interestingly, rigid rods over a wide range of composition were obtained even at low solids via aqueous polymerization of N ‐vinyl‐3‐dodecyl imidazolium bromide (C 12 VImBr) mediated by a neutral PEG‐CTA . b] These modular approaches by varying the cationic/anion moieties or the alkyl groups provide a new strategy for screening suitable monomers for dispersion polymerization.…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
“…For example, Clˉ and Brˉ counterions are considered as highly ionized ions for fixed polycations, while PF 6ˉ and bis(trifluoromethane)-sulfonimide (ˉNTf 2 ) are able to form tight ion pairs and turn cationic blocks insoluble in water but soluble in common organic solvents. [37][38][39][40][41][42] On the basis of this factor, the morphological structures of cation-containing polymers could be manipulated by simple anion exchange, which results from the tunable solubility of the ionic blocks. [43][44][45][46][47][48][49][50][51] For example, Vijayakrishna and co-workers found that the morphology of aggregates could be altered by exchanging of ˉN(SO 2 CF 3 ) 2 for Brˉ in imidazoliumbased ionic blocks.…”
Section: Doi: 101002/macp201800508mentioning
confidence: 99%
“…[34] While there are some examples for the polymerization of cationic vinyl monomers since 1970s, [35,36] it was only around the year 2000, pioneered by Ohno et al, that vinylimidazolium and vinylpyridinium salts were pursued as monomers for the creation of solid polymer electrolytes. [37][38][39] Since then, polymeric ionic liquids have become ubiquitous in the literature with research led by Long, [40][41][42][43] Texter, [44,45] Yuan, [46][47][48] Merceyyes, [30,49,50] Shaplov, [51][52][53][54][55] Drockenmuller, [56][57][58] and others to name a few. [59,60] The improved processability of polymers combined with the chemical utility and derivatizability of ionic liquids is the cornerstone for their interest and broader use.…”
Section: Polymeric Ionic Liquidsmentioning
confidence: 99%